AI 기반 스마트 하우징 플랫폼 및 서비스 기술 개발 방향 설정을 위한 기초 연구 - 안기언(Ki Uhn Ahn); 양현정(Hyeon-Jeong Yang); 채창우(Chang-U Chae) (KIEAE Journal, 2020)
Purpose: This study reviews publications on smart home related researches and services trends. The authors introduces a concept of smart housing platform in order to enhance the competitiveness and sustainability of smart home services and technologies. Method: The trend of smart home research is identified through literature reviews. The authors analyze the technical components of the smart housing platform by devices, gateways, networks, and services. In addition, issues of the current smart home are derived through the reviews on the smart home services strategies and AI based smart home technologies. In order to advance the competitiveness and sustainability of smart home, a smart housing platform is introduced based on the platform architecture, and a design of smart home service. Result: The smart housing platform will allow the diversity of networking through Open-Connectivity Integrated Gateway, and has the scalability for various participants to develop and register service modules. In addition, the personal information would be protected and managed by block chain technologies. KCI Citation Count: 2